PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERATING - Suprayitno, Dody Kristiawan & (Universitas Slamet Riyadi, 2009)
ABSTRACT This research aim to for the analyze of influence which is significant between : (1) Motivation to employees performance (2) Environment work to employees performance (3) Motivation and environment work by together to employees performance (4) Influence most dominant between environment and motivation have an effect on to Performance Employees with Leadership as moderaring variable.Its population is employees of PT WISANKA, Baki, Sukoharjo Year 2009 which is counted 50 people. Sample as a whole counted 50 employees. Technique data collecting by using enquette through validity test and reliabilities. Analysis technique use doubled linear regression test with assumption test classical.Conclusion result of research; (1) Hypothesis sounding motivation have an effect on positive and significant to proven employees performance. (2) Hypothesis sounding activity environment have an effect on positive and significant to employees performance (3) Hypothesis expressing leadership [is] dominant variable which have an effect on to proven employees performance. (4) Hypothesis expressing variable motivate and environment work by together have an effect on positive and significant to proven employees performance. (5) Hypothesis expressing environment and motivation work effect to employees performance with leadership as improvable moderating variable. Keywords: Motivation, work environmental, employees performance and leadership